2015
DOI: 10.1007/s10601-015-9215-9
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio approaches in constraint programming

Abstract: Recent research has shown that the performance of a single, arbitrarily efficient algorithm can be significantly outperformed by using a portfolio of -possibly onaverage slower-algorithms. Within the Constraint Programming (CP) context, a portfolio solver can be seen as a particular constraint solver that exploits the synergy between the constituent solvers of its portfolio for predicting which is (or which are) the best solver(s) to run for solving a new, unseen instance.In this thesis we examine the benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 150 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…Analogously, G +S is available on-line [119] but no longer developed. Conversely, the G-Strings solver [9] implementing the dashed string approach is actively maintained. Both G +S and G-Strings are extensions of Gecode [62], a well-established CP solver over finite domains.…”
Section: Practical Aspectsmentioning
confidence: 99%
“…Analogously, G +S is available on-line [119] but no longer developed. Conversely, the G-Strings solver [9] implementing the dashed string approach is actively maintained. Both G +S and G-Strings are extensions of Gecode [62], a well-established CP solver over finite domains.…”
Section: Practical Aspectsmentioning
confidence: 99%
“…Recent research in artificial intelligence areas, such as CP (Rossi et al, 2006), Boolean satisfiability (SAT) testing (Xu et al, 2007) and integer linear programming (ILP) (Wolsey, 1998), has shown that the performance of a sequential solver can be significantly improved by carefully exploiting a parallel solving architecture. In the literature, we can distinguish two mains approaches to exploit parallelism: divide-and-conquer and cooperative portfolio strategy (Amadini, 2015). In the former, the problem is divided into several sub-problems, each problem is solved separately and the result is later combined to form the solutions of the original problem, whereas the parallel portfolio strategy exploits the complementarily between different sequential solving strategies to let them compete and cooperate on the same problem.…”
Section: Parallel Portfolio Architecturementioning
confidence: 99%
“…We did not find in the literature suitable and extensive benchmarks of disaster scenarios that we could use to evaluate and compare the performances of our approach. For this reason, in order to evaluate our algorithm we extended the methodology used in [9]. In particular, we built random generated scenarios obtained by varying the number of hospitals in the set {1, 2, 4}, the number of ambulances in {4, 8, 16, 32, 64}, and the number of victims in {8, 16, 32, 64, 128, 256, 512}.…”
Section: Testsmentioning
confidence: 99%